The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1016/j.jneuroim.2004.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Complement C3 and C5 play critical roles in traumatic brain cryoinjury: blocking effects on neutrophil extravasation by C5a receptor antagonist

Abstract: The role of complement components in traumatic brain injury is poorly understood. Here we show that secondary damage after acute cryoinjury is significantly reduced in C3 −/− or C5 −/− mice or in mice treated with C5a receptor antagonist peptides. Injury sizes and neutrophil extravasation were compared. While neutrophil density increased following traumatic brain injury in wild type (C57BL/6) mice, C3-deficient mice demonstrated lower neutrophil extravasation and injury sizes in the brain. RNase protection ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
112
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 123 publications
(115 citation statements)
references
References 44 publications
(34 reference statements)
2
112
0
1
Order By: Relevance
“…As previously shown (20), cryo-injury to the brain disrupted the blood brain barrier immediately after insult, which induced brain edema followed by reactive gliosis in the present experimental model. In an intact region, testican-1 mRNA was clearly detected in hippocampal pyramidal neurons (Fig.…”
Section: Resultssupporting
confidence: 73%
“…As previously shown (20), cryo-injury to the brain disrupted the blood brain barrier immediately after insult, which induced brain edema followed by reactive gliosis in the present experimental model. In an intact region, testican-1 mRNA was clearly detected in hippocampal pyramidal neurons (Fig.…”
Section: Resultssupporting
confidence: 73%
“…Cytofluorimetric analysis showed that ϳ95% of cells were CD8 ϩ V␣2 ϩ T cells (OVA-specific) and Ͻ0.5% of them were CD11c ϩ after the depletion (data not shown). Lymphocytes were also isolated from organotypic culture as described previously (12). Lymphocytes were isolated from the slices and/or the harvested culture medium.…”
Section: Lymphocyte Isolationmentioning
confidence: 99%
“…Sewell et al [35] recently demonstrated that mice deficient in complement factor C3 expressed significantly lower levels of inflammatory cytokines than did wild-type mice, and complement inhibition has been shown to attenuate CNS injury, whether induced by external agents or genetic deficiency [1,25,43].…”
Section: Introductionmentioning
confidence: 99%